Pharmacists’ Awareness and Perceptions of Biosimilars in Saudi Arabia (Asian Journal of Pharmaceutics (AJP), 2020)
Objective: The current study aimed to evaluate practicing pharmacists’ awareness and perceptions aboutbiosimilars in Saudi Arabia. Materials and Methods: A cross-sectional study was performed using a prevalidatedand self-administered research tool by convenience sampling method. Registered pharmacists wereapproached to participate in the study. Descriptive and inferential statistics were performed using the StatisticalPackage for the Social Sciences version 24.0. P < 0.05 was considered statistically significant. Results: Out of319 pharmacists, 34.79% were familiar and 12.87% were very much familiar with the biosimilars. Around 33.22%were aware of the approval pathway and regulatory issues associated with prescribing biosimilars. The majorityof the respondents (>60%) had good awareness and positive perception toward biosimilars. Conclusion: Thisstudy concluded an appropriate awareness and positive perception toward biosimilars among pharmacists in SaudiArabia. Statistically non-significant association regarding biosimilars’ perception and awareness was observedbetween male and female pharmacists.